THE EFFECT OF BRAND AWARENESS, BRAND IMAGE, AND PERCEIVED QUALITY ON CUSTOMER SATISFACTION (STUDY ON CAFE Mr.K BSB) - Ardiansyah Ardiansyah; Mulyo Budi Setiawan (SEAN Institute, 2022)
This study aims to determine the effect of brand awareness, brand image, and perceived quality on mr. k bsb's customer satisfaction. the population of this research is the consumers of mr.k branch bsb, with the sample of this research is 100 customers of mr.k branch of bsb, with the sampling technique is quota sampling. the data collection method uses a likert scale, data collection is carried out using four scales, namely, customer satisfaction scale, brand awareness scale, brand image, and perceived quality. the regression equation obtained is y = 19.120 + 0.375 x1 + 0.283 x2 + 0.121 x3. based on the four hypotheses proposed, it is known that four hypotheses are accepted. the effective contribution of the three independent variables to the variable is 43.5%.